2018
DOI: 10.1007/s11207-018-1381-7
|View full text |Cite
|
Sign up to set email alerts
|

Flare Productivity of Major Flaring Solar Active Regions: A Time-Series Study of Photospheric Magnetic Properties

Abstract: A solar active region (AR) that produces at least one M-or X-class major flare tends to produce multiple flares during its passage across the solar disk. It will be interesting if we can estimate how flare-productive a given major flaring AR is for a time interval of several days, by investigating time series of its photospheric magnetic field properties. For this, we studied 93 major flaring ARs observed from 2010 to 2016 by the Helioseismic and Magnetic Imager (HMI) on board the Solar Dynamics Observatory (S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…On the other hand, a positive correlation exists between the average Φ and the average F idx with the linear PCC = 0.65 (refer to panel (b) of Figure 5). Such correlation of Φ with flaring activity in "individual" ARs has been reported in many previous studies (e.g., Leka & Barnes 2003Park et al 2010;Liu et al 2017;Lee et al 2018), but it is reported here for the first time on this larger spatial scale of the HRs over a much longer period of solar cycle 24. As shown in Figure 5(c), a negative, although weak, correlation appears between the HSP and the average Φ with the linear PCC = −0.36.…”
Section: Association Of the Hsp With Flaring Activity In Heliographic...supporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, a positive correlation exists between the average Φ and the average F idx with the linear PCC = 0.65 (refer to panel (b) of Figure 5). Such correlation of Φ with flaring activity in "individual" ARs has been reported in many previous studies (e.g., Leka & Barnes 2003Park et al 2010;Liu et al 2017;Lee et al 2018), but it is reported here for the first time on this larger spatial scale of the HRs over a much longer period of solar cycle 24. As shown in Figure 5(c), a negative, although weak, correlation appears between the HSP and the average Φ with the linear PCC = −0.36.…”
Section: Association Of the Hsp With Flaring Activity In Heliographic...supporting
confidence: 88%
“…Here N j is the total number of j-class flares assigned to the given AR sample during τ , and M j i is the magnitude (i.e., digit multipliers from 1.0 to 9.9) of the j-class flares. Simply put, F idx refers to the sum of GOES soft X-ray peak fluxes of all flares assigned to the given AR during τ , and it is often considered to measure flare productivity of an AR for a target interval (e.g., Abramenko 2005;Park et al 2010;Lee et al 2018).…”
Section: Assignment Of Flares To the Active Region Samplesmentioning
confidence: 99%
“…It should be noted in passing that various combinations of the many parameters utilized by Leka et al [2018] performed similarly well, within the error margins. Lee et al [2018] used a Detrended Fluctuation Analysis to remove persistent patterns and quantify the random variations in consecutive non-overlapping segments of time series. The detrended fluctuation and the time series averages were positively correlated with the imminent 8-day flare index.…”
Section: Quantifying the Temporal Evolution Of Active Regionsmentioning
confidence: 99%
“…It also provides a data product named Space-weather HMI Active Region Patch (SHARP), which offers a series of key parameters derived from the magnetic field in ARs (Bobra et al 2014;Hoeksema et al 2014). Lee et al (2018) applied I 8d , the sum of the GOES soft X-ray peak fluxes of flares in the same AR for 8 days, to investigate the correlation between SHARP parameters and flare productivity in time series, concluding that the SHARP parameters are to some extent related to flare productivity. Wang et al (2019) calculated the SHARP parameters in the polarity inversion line area of an AR, and employed a support vector machine algorithm to perform flare prediction with the modified SHARP parameters.…”
Section: Introductionmentioning
confidence: 99%